Ertapenem versus Standard Triple Antibiotic Therapy for the Treatment of Perforated Appendicitis in Pediatric Patients: A Prospective Randomized Trial - SANCAR, MESUT (GEORG THIEME VERLAG KG, 2014)
Background The primary objective of this study was to compare triple therapy with ertapenem treatments in pediatric patients with perforated appendicitis, especially in terms of postoperative infectious complications. The secondary objective of this study was to assess the relative impact of therapy with ertapenem and triple antibiotic regimen on the emergence of resistant bacteria in bowel flora in the patients. Materials and Methods Children aged 3 months to 17 years with perforated appendicitis were randomized 1: 1 to receive ertapenem or triple therapy. Serial rectal cultures were obtained from participants enrolled in the study, allowing assessment of the relative impact of therapy with ertapenem and triple therapy on bowel colonization by resistant bacteria. Results In this study, 107 patients were included. No difference existed in time to full oral intake and regular diet, the length of antibiotic therapy, the length of the postoperative hospitalization, or the length of hospital stay between the two groups. Patients in the triple-therapy group were more likely to suffer from a postoperative infectious complication than those in the ertapenem group (6/54 vs. 2/53, p > 0.05). Bowel colonization with resistant organisms at the end of therapy in the triple-therapy group was significantly different than in the ertapenem group (35.2 vs. 11.3%, p < 0.05). Conclusions Bowel colonization with resistant bacteria was less likely to occur after ertapenem treatment than triple therapy. The results of this trial suggest that ertapenem may be a useful option that could eliminate the need for combination and/or multidosed antibiotic regimens for the empiric treatment of perforated appendicitis in children.
Keywords: perforated appendicitis; children; ertapenem; bowel flora; VANCOMYCIN-RESISTANT ENTEROCOCCI; SPECTRUM BETA-LACTAMASE; GRAM-NEGATIVE BACILLI; IN-VITRO ACTIVITIES; INTRAABDOMINAL INFECTIONS; KLEBSIELLA-PNEUMONIAE; COMPLICATED APPENDICITIS; PSEUDOMONAS-AERUGINOSA; SUSCEPTIBLE ORGANISMS; INTESTINAL MICROFLORA